1990
DOI: 10.1105/tpc.2.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a rice gene showing organ-specific expression in response to salt stress and drought.

Abstract: Protein changes induced by salinity stress were investigated in the roots of the salt-sensitive rice cultivar Taichung native 1. We found eight proteins to be induced and obtained partia1 sequences of one with a molecular mass of 15 kilodaltons and an isoelectric point of 5.5. Using an oligonucleotide probe based on this information, a cDNA clone, sa/T, was selected and found to contain an open reading frame coding for a protein of 145 amino acid residues. sa/T mRNA accumulates very rapidly in sheaths and root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(95 citation statements)
references
References 37 publications
1
93
0
1
Order By: Relevance
“…The sequences of RCc2, RCc3 and ZRP3 are distinct from those previously described [2,6,7,8,14,19,21,23] for other root-specific clones and the biological functions of the encoded proteins are not known. However, the hydrophobic amino-terminal signal sequences present on the proteins encoded by RCc2 and RCc3 ( Fig.…”
Section: Rcc2 and Rcc3 Are Members Of An Evolutionarily Conserved Roomentioning
confidence: 86%
See 1 more Smart Citation
“…The sequences of RCc2, RCc3 and ZRP3 are distinct from those previously described [2,6,7,8,14,19,21,23] for other root-specific clones and the biological functions of the encoded proteins are not known. However, the hydrophobic amino-terminal signal sequences present on the proteins encoded by RCc2 and RCc3 ( Fig.…”
Section: Rcc2 and Rcc3 Are Members Of An Evolutionarily Conserved Roomentioning
confidence: 86%
“…Consequently, understanding plant root development and control mechanisms of root-specific gene expression is of importance for biotechnological approaches to crop improvement. Two productive approaches being used to address the limited knowledge in these areas are the identification of root mutants [26] and the isolation and characterization of root-specific genes [2,6,7,8,14,18,19,21,23]. A few genes have been isolated that are preferentially expressed in roots for which the functions are known.…”
Section: Introductionmentioning
confidence: 99%
“…Plants are known to respond to salt stress by an increase in net synthesis of some proteins and a decrease in the synthesis of others, with or without a concomitant induction of certain specific stress proteins (Ericson & Alfinito 1984;Singh et al, 1985;Ramagopal, 1986;Hurkman & Tanaka, 1987;Ramagopal, 1987;Hurkman et al, 1988;Winicov et al, 1989;Claes et al, 1990;Roy et al, 1990;Godoy et al, 1991). However, reports on salinity induced changes in gene expression in isogenic lines differing in salt-tolerance are scarce (Ericson & Alfinito, 1984;Singh et al, 1985;Winicov et al, 1989.…”
Section: Discussionmentioning
confidence: 99%
“…Hurkman et al (1988) suggested that such proteins may be involved in a selective transport of K + and Na ÷ across the plasma membrane or the tonoplast. A better understanding of the role that altered protein pattern/ gene expression plays in salt tolerance can be achieved when the genes or mRNAs coding for salt related or induced proteins are identified and characterized (Winicov et al, 1989;Claes et al, 1990;Godoy et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation